Efektivitas Komunikasi Tim Ranger dalam Sosialisasi Core Values Akhlak kepada Karyawan - Intan Mayasa; Erik Setiawan (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. As stipulated in the Circular Letter of the Minister of SOEs Number: SE 7/MBU/07/2020 dated July 1, 2020 regarding the Core Valuess of Human Resources of State-Owned Enterprises, all SOEs including PT. X Parent Unit for South Sulawesi, Southeast Sulawesi and West Sulawesi Regions are required to apply the main valuess of AKHLAK as Corporate Culture, the Ranger Team has the responsibility to socialize them. The purpose of this study was to determine the effectiveness of the Ranger Team's communication in socializing the core valuess of AKHLAK to employees. The research method used is quantitative with a descriptive study approach. Data collection techniques obtained in the form of research questionnaires with 63 respondents and literature studies relevant to this research. The dimensions of communication effectiveness measured in this study are known as